Relevant predisposing factors for voiding in a sitting position among Japanese male adult patients - Motofumi Suzuki; Taichi Shiratori; Akihiro Naito (Continence, 2022)
Purpose:: We investigated the proportion of male patients who urinate in a sitting position and their reasons for doing so. Furthermore, we analyzed relevant predisposing factors for voiding in a sitting position using voiding questionnaires and uroflowmetric parameters. Material and methods:: Study participants included 370 male patients who underwent examination of uroflowmetry and measurement of post-void residual urine volume. We asked the participants to urinate in a standing or sitting position as they would usually do at home and their reasons for the voiding posture selected. Results:: Among the participants, 38.6% (143/370 cases) urinated in a sitting position. The most common reason for voiding in a sitting position was to keep the bathroom clean (54.5%, 78/143 cases). Compared with the participants who urinate in a standing position, significantly lower body mass index, and longer times of hesitancy and voiding were observed in the participants who urinate in a sitting position. Relevant predisposing factors for voiding in a sitting position were higher maximum flow rate and longer times of hesitancy and voiding. Conclusions:: Uroflowmetric parameters, including maximum flow rate and longer times of hesitancy and voiding, were associated with the preference of a sitting voiding position in Japanese male adult patients.